Energy harvesting performance of piezoelectric electrospun polymer fibers and polymer/ceramic composites - Nunes-Pereira, João (2013)
The energy harvesting efficiency of electrospun poly(vinylidene fluoride), its copolymer vinylidene fluoride-trifluoroethylene and composites of the later with piezoelectric BaTiOon interdigitated electrodes has been investigated. Further, a study of the influence of the electrospinning processing parameters on the size and distribution of the composites fibers has been performed. It is found that the best energy harvesting performance is obtained for the pure poly(vinylidene fluoride) fibers, with power outputs up to 0.03 W and 25 W under low and high mechanical deformation. The copolymer and the composites show reduced power output due to increased mechanical stiffness. The obtained values, among the largest found in the literature, the easy processing and the low cost and robustness of the polymer, demonstrate the applicability of the developed system.